Treponema pallidum genetic diversity and its implications for targeted vaccine development: A cross-sectional study of early syphilis cases in Southwestern Colombia - Salazar, Juan C.; Vargas-Cely, Fabio; García-Luna, Jonny A.; Ramirez, Lady G.; Bettin, Everton B.; Romero-Rosas, Nelson; Amórtegui, María F.; Silva, Sebastián; Oviedo, Oscar; Vigil, Julie; La Vake, Carson J.; Galindo, Ximena; et al. (PloS one, 2024)
Venereal syphilis, caused by the spirochete Treponema pallidum subsp. pallidum (TPA), is surging worldwide, underscoring the need for a vaccine with global efficacy. Vaccine development requires an understanding of syphilis epidemiology and clinical presentation as well as genomic characterization of TPA strains circulating within at-risk populations. The aim of this study was to describe the clinical, demographic, and molecular features of early syphilis cases in Cali, Colombia. We conducted a cross-sectional study to identify individuals with early syphilis (ES) in Cali, Colombia through a city-wide network of public health centers, private sector HIV clinics and laboratory databases from public health institutions. Whole blood (WB), skin biopsies (SB), and genital and oral lesion swabs were obtained for measurement of treponemal burdens by polA quantitative polymerase chain reaction (qPCR) and for whole-genome sequencing (WGS). Among 1,966 individuals screened, 128 participants met enrollment criteria: 112 (87%) with secondary (SS), 15 (12%) with primary (PS) and one with early latent syphilis; 66/128 (52%) self-reported as heterosexual, while 48 (38%) were men who have sex with men (MSM). Genital ulcer swabs had the highest polA copy numbers (67 copies/μl) by qPCR with a positivity rate (PR) of 73%, while SS lesions had 42 polA copies/μl with PR of 62%. WB polA positivity was more frequent in SS than PS (42% vs 7%, respectively; p = 0.009). Isolation of TPA from WB by rabbit infectivity testing (RIT) was achieved in 5 (56%) of 9 ES WB samples tested. WGS from 33 Cali patient samples, along with 10 other genomic sequences from South America (9 from Peru, 1 from Argentina) used as comparators, confirmed that SS14 was the predominant clade, and that half of all samples had mutations associated with macrolide (i.e., azithromycin) resistance. Variability in the outer membrane protein (OMP) and vaccine candidate BamA (TP0326) was mapped onto the protein's predicted structure from AlphaFold. Despite the presence of mutations in several extracellular loops (ECLs), ECL4, an immunodominant loop and proven opsonic target, was highly conserved in this group of Colombian and South American TPA isolates. This study offers new insights into the sociodemographic and clinical features of venereal syphilis in a highly endemic area of Colombia and illustrates how genomic sequencing of regionally prevalent TPA strains can inform vaccine development.